2015
DOI: 10.1016/j.vetmic.2015.01.022
|View full text |Cite
|
Sign up to set email alerts
|

First study of pathogen load and localisation of ovine footrot using fluorescence in situ hybridisation (FISH)

Abstract: HighlightsFirst FISH study of ovine FR to examine pathogen spatial distribution and load.D. nodosus cell counts are significantly associated with both ID and SFR.F. necrophorum cell counts are significantly associated with SFR.Highlights FISH as a useful tool for studying microbial populations in situ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 32 publications
6
23
0
1
Order By: Relevance
“…Studies using whole biopsies reported eubacteria presence in healthy ovine interdigital skin (Calvo-Bado et al 2011;Maboni et al 2016;Witcomb et al 2015). Interestingly, we detected eubacterial DNA down to depths of 3mm in healthy samples.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Studies using whole biopsies reported eubacteria presence in healthy ovine interdigital skin (Calvo-Bado et al 2011;Maboni et al 2016;Witcomb et al 2015). Interestingly, we detected eubacterial DNA down to depths of 3mm in healthy samples.…”
Section: Discussionmentioning
confidence: 53%
“…Previous studies based on Giemsa stain and fluorescent in situ hybridisation (FISH) have suggested D. nodosus was primarily localised in superficial epidermis of ovine interdigital skin (Egerton et al 1969;Witcomb et al 2015). However, Witcomb and colleagues reported a single cell of D.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variability of reduction within disinfectant groups was observed and is explainable by various factors influencing the ex vivo experiment. D. nodosus loads vary naturally among feet due to individual differences and the different clinical status of footrot affected feet, leading to different prevalues [28]. Furthermore, the total number of microorganisms can also affect the activity of a disinfectant.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently the pathogenesis of footrot was thought to be due to an initial infection by F. necrophorum followed by a secondary infection with D. nodosus (11), but recent studies suggest otherwise. Regardless, both bacteria play an important role in footrot infection, with D. nodosus possibly driving the pathogenesis of footrot from the initiation of interdigital dermatitis through to the development of severe footrot, and F. necrophorum likely attributing to the severity and duration of the infection (12,13). In cases of foot abscesses, F. necrophorum has been associated in conjunction with T. pyogenes (8,14).…”
Section: Introductionmentioning
confidence: 99%